AZFa candidate gene UTY and its X homologue UTX are expressed in human germ cells - Peter H Vogt; Jutta Zimmer; Ulrike Bender; Thomas Strowitzki (Bioscientifica, 2021)
The Ubiquitous Transcribed Y (UTY a.k.a. KDM6C) AZFa candidate gene on the human Y chromosome and its paralog on the X chromosome, UTX (a.k.a. KDM6A), encode a histone lysine demethylase removing chromatin H3K27 methylation marks at genes transcriptional start sites for activation. Both proteins harbour the conserved Jumonji C (JmjC) domain, functional in chromatin metabolism, and an extended N-terminal tetratricopeptide repeat (TPR) block involved in specific protein interactions. Specific antisera for human UTY and UTX proteins were developed to distinguish the expression of both proteins in human germ cells by immunohistochemical experiments on appropriate tissue sections. In the male germ line, UTY was expressed in the fraction of A spermatogonia located at the basal membrane, probably including spermatogonia stem cells. UTX expression was more spread in all spermatogonia and in early spermatids. In female germ line, UTX expression was found in the primordial germ cells of the ovary. UTY was also expressed during fetal male germ cell development, whereas UTX expression was visible only at distinct gestation weeks. Based on these results and the conserved neighboured location of UTY and DDX3Y in Yq11 found in mammals of distinct lineages, we conclude that UTY, such as DDX3Y, is part of the Azoospermia factor a (AZFa) locus functioning in human spermatogonia to support the balance of their proliferation-differentiation rate before meiosis. Comparable UTY and DDX3Y expression was also found in gonadoblastoma and dysgerminoma cells found in germ cell nests of the dysgenetic gonads of individuals with disorders of sexual development and a Y chromosome in karyotype (DSD-XY). This confirms that AZFa overlaps with GBY, the Gonadoblastoma susceptibility Y locus, and includes the UTY gene.